DEVELOPMENT OF TEACHERS’ INFORMATION AND COMMUNICATION COMPETENCE IN GENERAL SECONDARY EDUCATION OF THE NETHERLANDS: APPROACHES, MODELS, EXPERIENCE - Olena O. Grytsenchuk (Інформаційні технології і засоби навчання, 2015)
The article deals with the problem of teacher’s information and communication competence development in general secondary education of the Netherlands. The analysis of the experience of such national institutions as Expertise Centre of ICT Education, Fund Kennisnet, SchoolNet of the Netherlands, Netherlands Institute for Curriculum Development (SLO), General Consultative Body of Heads of Teachers Educational Faculties is presented. There are identified peculiarities, common trends, approaches and models of teacher’s information and communication competence, as well as the ways of teacher’s information and communication competence future development in general secondary education of the Netherlands.